2019
DOI: 10.1002/mame.201900505
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dielectric Constant and Low‐Temperature Curable Polyimide/POSS Nanocomposites

Abstract: With the rapid development of ultra large scale integrated circuits, low stress, low thermal expansion, low dielectric constant, and low temperature curable (<250 °C) polyimides (PIs) with excellent mechanical, thermal properties are required. Unfortunately, high curing temperatures above 300 °C and limited dielectric property still remain to be solved. Herein, a new type of aminopropyl isobutyl polysilsesquioxane (POSS) with single vertex activity is introduced by in situ polymerization resulting in the PI‐PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…In the second way, air void structures were introduced into PI matrix to reduce dielectric constant and loss, as the dielectric constant ( ε ) of air is approximately 1.0 22,23 . Among them, Kung‐Hwa Wei et al 16,24 and our group 25 brought polyhedral oligomeric silsesquioxane (POSS) into the PI, greatly decreasing the permittivity. However, the mechanical properties of PI with porous structure are severely impaired for interlayer dielectric (ILD) material applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the second way, air void structures were introduced into PI matrix to reduce dielectric constant and loss, as the dielectric constant ( ε ) of air is approximately 1.0 22,23 . Among them, Kung‐Hwa Wei et al 16,24 and our group 25 brought polyhedral oligomeric silsesquioxane (POSS) into the PI, greatly decreasing the permittivity. However, the mechanical properties of PI with porous structure are severely impaired for interlayer dielectric (ILD) material applications.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple researchers have suggested that nanoparticles such as POSS, which have a hollow, porous core and high steric volume, increase the space between polymer chains and reduce inter‐polymer interactions, resulting in an increase in free volume in the nanocomposites 51–57 . The lower dipole strengths and the decreased number density of effective dipoles (reduced dielectric relaxation strength) seen in the PES/POSS blends could be attributed to an increase in free volume.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple researchers have suggested that nanoparticles such as POSS, which have a hollow, porous core and high steric volume, increase the space between polymer chains and reduce inter-polymer interactions, resulting in an increase in free volume in the nanocomposites. [51][52][53][54][55][56][57] The lower dipole strengths and the decreased number density of effective dipoles (reduced dielectric relaxation strength) seen in the PES/POSS blends could be attributed to an increase in free volume. Other groups propose that favorable interactions between the nanoparticles and the polymer matrix confine and immobilize the polymer chains at the nanoparticlepolymer interface and thus diminish the polarizability and dielectric relaxation strength of the polymer matrix.…”
Section: Dielectric Spectroscopymentioning
confidence: 99%
“…S1(a). † The characteristic absorption peak of EPPOSS@Gh-BN is detected at 1116 cm À1 , which is evidence of the presence of Si-O-Si vibration, 40 conrming that EPPOSS was successfully graed onto the surface of Gh-BN. The formation of EPPOSS by VIPOSS epoxidation reaction was conrmed by the absorption peaks at 1604 cm À1 (-C]C vibration) and 870 cm À1 (C-O-C symmetric and asymmetric stretching vibration), as shown in Fig.…”
Section: Structural Analysismentioning
confidence: 91%
“…38 Polyhedral oligomeric silsesquioxane (POSS) is an organicinorganic hybrid nanomaterial that has been widely studied as an effective ller for low dielectric polymer composites owing to its unique hollow structure. 39,40 In particular, the inorganic cubic-cage core provides mechanical properties. 41 Guo et al 42 used KH560 to modify h-BN, and then combined the amino group on the NH 2 -POSS molecule with the epoxy group on KH560 to obtain POSS-modied h-BN (f-BN) successfully.…”
Section: Introductionmentioning
confidence: 99%